2020
DOI: 10.1371/journal.pone.0233913
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in total leukocytes in malaria patients compared to febrile controls: A systematic review and meta-analysis

Abstract: Background Leukocyte alterations are a common hematological alteration among malaria patients. Objectives This systematic review and meta-analysis aimed to provide data and evidence comparing alterations in total leukocyte counts in malaria patients compared to febrile/healthy subjects at baseline before treatment. A systematic review was conducted by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement for reporting systematic reviews and meta-analyses. Data sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Nevertheless, the meta-analysis of those two studies 47 , 48 demonstrated a higher leukocyte count in P. ovale curtisi infection than in P. ovale wallikeri infection. A previous study reported a reduction in total leukocyte counts during malaria infection 66 . In the present study, although the results demonstrated the difference in the mean leukocyte counts between P. ovale curtisi and P. ovale wallikeri malaria, the interpretation could not be made because only a small number of cases were investigated, or the difference suggested that P. ovale curtisi infection induces a higher immune response in patients than P. ovale wallikeri infection.…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, the meta-analysis of those two studies 47 , 48 demonstrated a higher leukocyte count in P. ovale curtisi infection than in P. ovale wallikeri infection. A previous study reported a reduction in total leukocyte counts during malaria infection 66 . In the present study, although the results demonstrated the difference in the mean leukocyte counts between P. ovale curtisi and P. ovale wallikeri malaria, the interpretation could not be made because only a small number of cases were investigated, or the difference suggested that P. ovale curtisi infection induces a higher immune response in patients than P. ovale wallikeri infection.…”
Section: Discussionmentioning
confidence: 85%
“…Thrombocytopenia occurs in approximately 80% of patients infected with either severe or uncomplicated malaria [45]. Lymphopenia and high neutrophil per lymphocyte ratios occur in malaria patients [41], and previous studies have also frequently noted lymphopenia in severe COVID-19 patients [46,47]. Such cases of lymphopenia indicate low T and B cell counts [48][49][50], which may be caused by coronaviruses affecting bone marrow precursors directly, resulting in increased auto-immune response against blood cell precursors [51,52].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Additionally, COVID-19 infected patients have a higher proportion of laboratory alterations than those of co-infected individuals such as CRP, D-dimer, AST, and ALT. Nevertheless, thrombocytopenia, lymphopenia, mild anemia, elevated bilirubin, elevated D-dimer, and elevated ferritin were observed in Plasmodium monoinfected individuals [41][42][43][44]. Therefore, it is not clear whether laboratory parameters could be semi-diagnostic parameters for COVID-19 and Plasmodium co-infected individuals.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Symptoms on admission in this case series were similar to those previously reported [ 3 , 15 ], being anemia and thrombocytopenia two common laboratory alterations among pregnant women with this co-infection [ 3 ]. It is unclear whether laboratory parameters could help discriminate malaria and COVID-19 co-infection [ 3 ], since some laboratory alterations may be more common in SARS-CoV-2 mono-infected than in co-infected patients and yet other more frequent in malaria mono-infected patients [ 17 20 ].…”
Section: Discussionmentioning
confidence: 99%